Stir what you've got : insights from a college president - Greer, William T., Jr (Identity & practice in higher education-student affairs., 2023)
"These are stories about an average young man who grew up among talented people. These talented people raised him and so many others. We were exceptional in that we picked up their dreams for us and made them ours. We became the farmers, lawyers, doctors and teachers who made our town and South Georgia very special. This volume reminds us that dreams can come true. This was probably the last generation of teachers- mostly women- who opened the door of hope far wider than any of us had ever dreamed. We were among so many brilliant people. Regardless of where you grew up, you had teachers like them. For me, there were people like Mrs. Mitchell, Mrs. Crum, Coaches Davis and Tucker, Mrs. Agnew Andrews Brown, Mrs. Tabor and a host of others. Our parents gave us opportunities they never had. Every name in these pages made a huge difference in the lives they touched. Our world needs again and again what we found in our little country town. May those hearing these stories for the first, second or third time be inspired to tell them over and over again. They are your stories. Claim them"--